Zonation Drives The Abundance of Understory Exotic Plant Species in Ir. Djuanda Forest Park, West Java - Tri Cahyanto; Billy Nabil Yuni; Muhammad Efendi (Elkawnie, 2021)
Abstract: The understory is an important component in the tropical forests, particularly to contribute to ecosystem services function and playing on succession. However, the study on their existence related to the zonation effect in an ex-situ conservation is still lacking. This study aimed to compare the structure and composition of the understory in the two blocks of Ir. Djuanda Forest Park, Bandung. Data collection was carried out through vegetation analysis using plot methods (sampling plots). A total of 40 sampling plots of 5m x 5m were made in two observation blocks. The Importance Value Index (IVI) for each species was calculated based on their relative density and relative frequency. Seventy-three species of understory from 38 families were found in the observation plots, dominated by Araceae and Moraceae families. The composition of the protected block has higher species richness than the utilization block due to the differences in microclimates conditions. Calliandra calothyrsus, known as an invasive species, has the highest IVI indicating high adaptability to open habitats in the utilization block, while two native species, Plectranthus sp. and Chlorathus elatior, dominate in the protection block. Based on these findings, we showed that forest zonation drives exotic and native species abundance in the ex situ conservation area.Abstrak: Tumbuhan bawah merupakan salah satu komponen penting dalam vegetasi hutan tropis, terutama dalam pelayanan ekosistem dan berperan dalam proses suksesi. Namun, penelitian mengenai keberadaannya dikaitkan dengan pengaruh zonasi di kawasan konservasi secara ex situ masih jarang. Tujuan penelitian ini untuk membandingkan struktur dan komposisi tumbuhan bawah pada dua blok yang berbeda di kawasan Taman Hutan Raya Ir. Djuanda, Bandung. Pengambilan sampel menggunakan analisis vegetasi dengan metode plot (petak contoh). Sebanyak 40 plot kecil berukuran 5mx5m di kedua blok pengamatan. Indeks nilai penting (INP) setiap jenis dihitung berdasarkan kerapatan relatif dan frekuensi relatifnya. Sebanyak 73 jenis dalam 38 suku tumbuhan didata di dalam pengamatan, yang didominasi dari suku Araceae dan Moraceae. Berdasarkan jumlah jenis tumbuhan penyusunnya, blok perlindungan memiliki jenis yang lebih banyak dibandingkan dengan blok pemanfaatan berkaitan dengan berkaitan dengan perbedaan kondisi iklim mikro di kedua blok tersebut. Jenis Calliandra calothyrsus, dikenal sebagai tumbuhan invasif, memiliki nilai INP tertinggi menunjukkan kemampuan adaptasi yang tinggi pada habitat terbuka di blok pemanfaatan, sedangkan tumbuhan asli pegunungan jawa, Plectranthus sp. dan Chloranthus elatior mendominasi pada blok perlindungan. Berdasarkan hasil temuan ini, kita menyarankan bahwa zonasi mempengaruhi kelimpahan tumbuhan eksotik dan asli di kawasan konservasi tumbuhan secara eksitu.